2017
DOI: 10.1128/aac.01988-16
|View full text |Cite
|
Sign up to set email alerts
|

Ethambutol Is Cleared by a Contemporary High-Flux Hemodialyzer, and Drug Monitoring Ensures Safety and Therapeutic Effect

Abstract: It is uncertain, given the lack of recent data and the inconclusive nature of previous data, whether ethambutol is cleared by hemodialysis using contemporary dialyzers. We measured serum ethambutol concentrations before, during, and 1 h after hemodialysis in a 75-year-old Caucasian man receiving ethambutol for disseminated Bacille Calmette-Guérin infection. There was a mean 41% decrease in serum ethambutol concentration during dialysis, confirming the hemodialyzability of ethambutol and the utility of drug mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Interestingly, according to Park et al, this incidence increases to 17% when a liver disease coexists, irrespective of the presence or absence of cirrhosis [ 48 ]. In contrast, ethambutol is not associated with clinically important hepatotoxic effects [ 25 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, according to Park et al, this incidence increases to 17% when a liver disease coexists, irrespective of the presence or absence of cirrhosis [ 48 ]. In contrast, ethambutol is not associated with clinically important hepatotoxic effects [ 25 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 80% of EMB is eliminated unchanged by the kidney,10 but in patients with compromised renal function, the clearance of EMB significantly decreases and its half-life is prolonged following the usual dosage of 15 mg/kg 11. One recent study reported a 41% decrease in serum ethambutol concentration during dialysis in a patient using contemporary High-Flux Hemodialyzer 12. A pharmacokinetic study of one CAPD patient found that 35.3% of EMB is eliminated by peritoneal dialysis 13…”
Section: Discussionmentioning
confidence: 99%
“…This agent is metabolised into a less active compound by n-acetyltransferase in the liver and then eliminated by the kidneys. Pharmacokinetic studies on haemodialysis patients have found that only 9.2% of INH is recovered in dialysate, which suggests that hepatic metabolism is the primary mechanism for the clearance of INH 12. Peritoneal dialysis is responsible for 1.3% of all INH clearance; the concentration of INH in the peritoneal fluid after 6 hour of dwell time reaches 53.3% of its simultaneous serum concentration 27…”
Section: Discussionmentioning
confidence: 99%
“…Given the risk for ocular toxicity, consideration may be given to substituting moxifloxacin for ethambutol in patients with renal dysfunction. TDM has been suggested for guiding therapy in patients receiving dialysis [180,181].…”
Section: Tdm In Patients With Renal Impairmentmentioning
confidence: 99%